Designing the Classic Teaching Session for Architectural Student via New BOPPPS Model with the Spirit “S” or Seventh Seal - Gunerathne, Ravindra; Marikar, Faiz (Educational Challenges, 2023)
Purpose is to analyze BOPPPS as a model for participatory learning and development (PLD) activities for architectural students. Methodology. The methods of analysis, classification, and descriptions are used. Results. BOPPPS model consists of the following components: Bridge-in: An opening session to introduce the topic, participants, and objectives of the PLD activity. Objectives: Defining the specific goals and outcomes that the PLD activity aims to achieve. Post-test: An evaluation tool used to assess participants' knowledge and understanding of the topic prior to the PLD activity. Participatory Learning: A process where participants actively engage in learning activities, such as group discussions, role-plays, and hands-on exercises, to acquire new knowledge and skills. Post-assessment: An evaluation tool used to assess participants' knowledge and understanding of the topic after the PLD activity. Summary: A closing session where the facilitator summarizes the key takeaways from the PLD activity and highlights areas for further improvement or follow-up. The BOPPPS model is designed to ensure that PLD activities are well-structured, participatory, and effective in promoting learning and development. By incorporating evaluation tools such as pre- and post-tests, the model allows organizers to measure the impact of the PLD activity and assess its effectiveness. The addition of the "S for Spirit" in the BOPPPS model emphasizes the importance of designing PLD activities with the spirit, or the essence and guiding principle, of the project. This means that the PLD activity is not only structured and evaluated effectively, but also aligns with the purpose, values, and vision of the project. Designing with the spirit can add a more meaningful and personal touch to the PLD activity, creating a more impactful learning experience for participants. Conclusions. The updated BOPPPS model could include one more component Spirit (S). They are as followings: Bridge-in, Objectives, Post-test, Participatory Learning, Post-assessment, Summary, and definitely Spirit (S) – the guiding principle and essence of the project that shapes the PLD activity.